Plant Sterols/Stanols: Do they have a Role in Current Cardiovascular Disease Prevention? - Filippatos, Theodosios D.; Elisaf, Moses S. (Journal of Nutritional Therapeutics, 2015)
Plant sterols/stanols inhibit cholesterol absorption in the gastrointestinal tract. The daily consumption of 2 g/day of plant sterols/stanols decreases low-density lipoprotein cholesterol (LDL-C) levels by approximately 10%. Plant sterols/stanols also reduce LDL-C levels when co-administered with statins, a fact useful for patients intolerable to high-dose statins. However, no randomized, controlled clinical trials have examined the clinical benefit of daily consumption of plant sterols/stanols. Furthermore, concerns regarding a possible atherogenic effect of plant sterols have been expressed. The use of plant sterols/stanols-enriched foods is a useful adjunct for hypercholesterolemic patients to achieve their LDL-C target, but we need more data to establish if this hypolipidemic effect results to reduced cardiovascular risk.